Učno okolje, ki omogoča kakovostno samostojno učenje - Kerndl, Milena (Revija za elementarno izobraževanje, 2010)
Learning environments that enable quality independent learning. It is not the classroom of pupils that is emphasized in teaching; it is the learning society that is being focused on. Learning situations are produced in which the teacher provides learners with authentic tasks that represent learning challenges while at the same time increase intrinsic motivation. The teacher used to be the only source of information, but now this role has changed. Nowadays the teacher is a guide, advisor, promoter, instructor, listener, moderator, organizer, etc. They are not only content experts, but also observers who know a lot about interpersonal relations so that they can adjust the learning process to the learners’ abilities, needs and interests. By using active teaching methods, the teacher should make sure that these methods answer the purpose of a particular topic. They should carefully choose and combine methods / strategies (and produce such a learning environment) that will optimally lead to the set goals (educational and functional). The article first deals with some theoretical starting points of modern teaching, which are then applied to a Slovene language class by discussing a humoresque.